2018
DOI: 10.1128/jcm.00787-17
|View full text |Cite
|
Sign up to set email alerts
|

The Alere BinaxNOW Pneumococcal Urinary Antigen Test: Diagnostic Sensitivity for Adult Pneumococcal Pneumonia and Relationship to Specific Serotypes

Abstract: Little is known about the sensitivity of the BinaxNOW pneumococcal urinary antigen (PUA) test for adult pneumococcal pneumonia caused by different serotypes. In this study, we aimed to analyze the trends in the sensitivity of the PUA test over a 15-year period (2001 to 2015) and to analyze its sensitivity for pneumococcal pneumonia caused by different serotypes. In total, we analyzed 1,096 pneumococcal isolates from adults with pneumococcal pneumonia who had a PUA test performed at the onset of the episode. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 18 publications
(20 reference statements)
2
25
0
1
Order By: Relevance
“…There is evidence suggesting that UAT is less sensitive following the introduction of the 13-valent polysaccharide conjugate vaccine (PCV-13), with the sensitivity of UAT varying from 33.1% to 100% depending on the serotype [20]. The sensitivity of BinaxNOW ® to S. pneumoniae serotypes not included in PCV-13 was below 70% in this study [20].…”
Section: Accuracymentioning
confidence: 54%
See 1 more Smart Citation
“…There is evidence suggesting that UAT is less sensitive following the introduction of the 13-valent polysaccharide conjugate vaccine (PCV-13), with the sensitivity of UAT varying from 33.1% to 100% depending on the serotype [20]. The sensitivity of BinaxNOW ® to S. pneumoniae serotypes not included in PCV-13 was below 70% in this study [20].…”
Section: Accuracymentioning
confidence: 54%
“…Several studies published after the meta-analysis have found the sensitivity of the BinaxNOW ® UAT to be between 60% and 65% [18,19], significantly lower than that found by SINCLAIR et al [17]. There is evidence suggesting that UAT is less sensitive following the introduction of the 13-valent polysaccharide conjugate vaccine (PCV-13), with the sensitivity of UAT varying from 33.1% to 100% depending on the serotype [20]. The sensitivity of BinaxNOW ® to S. pneumoniae serotypes not included in PCV-13 was below 70% in this study [20].…”
Section: Accuracymentioning
confidence: 96%
“…However, on repeat testing the 11A/C/E or serogroup 16 antigen was detected below the positivity cut-off whilst the serotype 5 antigen was detected just above the cut-off, and therefore the sample was reported as positive for the serotype 5 antigen only. The BinaxNOW pneumococcal test can detect pneumococcal cell-wall C polysaccharide in urine and cerebrospinal fluid (CSF) samples with reported sensitivities of 74–90 % and specificities of 71–97 % [ 20–23 ], although sensitivities may vary in relation to the serotype [ 23 ]. In total, 412 urine samples tested positive for the pneumococcal antigen with the BinaxNOW test and 374 (90.8 %) of these were positive for a pneumococcal serotype and/or CWP antigen with the BioPlex assay.…”
Section: Resultsmentioning
confidence: 99%
“…11 The same CAP guidelines encourage attempts to broaden, narrow or modify the spectrum of antibiotic therapy based on diagnostic test results, but traditional microbiological investigations have significant limitations and little influence on patient management. [12][13][14] Indeed, a randomised trial of 177 patients found that the routine implementation of urine antigen detection tests did not bring any substantial disease or economic-related benefits to patients hospitalised with CAP. 15 Significantly, CAP is one of the leading causes of antibiotic prescribing, and often, the causative agent is not early identified and patients are overtreated.…”
Section: Open Accessmentioning
confidence: 99%